A feminist materialist inspired analysis of the meaning and management of pregnancy and reproductive health in Olympic and Paralympic female athletes - Pullen, E.; Miller, B.; Wiltshire, G.; Plateau, C. (Qualitative Research in Sport, Exercise and Health, 2023)
The number of elite female athletes returning to professional sport following childbirth has gradually increased in recent years. There now exists a burgeoning of scholarship across sport and health-related disciplines that have paid attention to the experiences of pregnancy and motherhood in elite female athlete populations. This paper contributes to this expanding topic of inquiry by taking inspiration from feminist materialist approaches to examine the experiences and politics of pregnancy and reproductive health in elite female Olympic and Paralympic athletes on the United Kingdom elite sport funded programme - The World Class Programme (WCP). In doing so, we begin to foreground the bio-social-material practices and entanglements that constitute the WCP environment which actively shape athletes` understandings of reproductive health and choice around pregnancy in particular ways. We discuss how the presented data has implications for female athlete embodied subjectivity and reproductive realities that complicate cultural narratives around athlete agency and gender equities in elite sport.